A case report and literature review of immune checkpoint inhibitor-associated pneumonia caused by penpulimab - Gao, Rongmao; Yang, Fuxun; Yang, Chen; Zhang, Zhao; Liu, Mingzong; Xiang, Chunlin; Hu, Huan; Luo, Xiaoxiu; Li, Jiajia; Liu, Rongan (Frontiers in Immunology, 2023)
Objective From the perspective of intensive care physicians, this paper reviews the diagnosis and treatment of CIP patients, analyzes and refines relevant literature on CIP. To summarize the characteristics of diagnosis and treatment of severe CIP provides the basis and reference for early identification, diagnosis and treatment. Methods A case of severe CIP caused by piamprilizumab and ICI was reviewed and the literature was reviewed. Results This was a patient with lung squamous cell carcinoma with lymphoma who had been treated with multiple chemoradiotherapy and immunotherapy with piamprizumab. The patient was admitted to the ICU with respiratory failure. The intensive care physician performs anti-infective, fluid management, hormonal anti-inflammatory, respiratory and nutritional support treatment, and relies on mNGS to exclude severe infection and CIP treatment, thus successfully saving the patient's life and improving discharge. Conclusions The incidence of CIP is very low, and its diagnosis should be combined with clinical manifestations and previous drug use. mNGS can provide certain value in the exclusion of severe infections, so as to provide basis and reference for the early identification, diagnosis and treatment of severe CIP.